Design and experiment verification of OR‐PM machine with rectangular shaped magnets for integrated power generation. Issue 4 (25th February 2020) - Wang, Chen; Geng, Weiwei; Zhang, Zhuoran
Abstract : Outer‐rotor permanent‐magnet (OR‐PM) machines provide several distinct advantages such as high torque density and large rotor inertia due to the large outer diameter of effective air gap for power conversion. The purpose of this study is to replace flywheel with the outer rotor by adopting OR‐PM machines since this topology is well‐suited for integration with diesel engines. This study specifically investigates a 16‐pole–18‐slot ring‐shaped PM motor with rectangular shaped PM rotor for integrated power generation application. At first, the pole arc, rotor yoke thickness and PM slot height of the OR‐PM machine with rectangular shaped PM are optimised. In addition, the no‐load magnetic field, cogging torque and back‐electromotive force of the OR‐PM machine with rectangular shaped PM and have been analysed and compared based on two‐dimensional finite element analysis. Additional comparison including torque characteristics, field weakening, cost and efficiency are also highlighted. The results show that the OR‐PM machine with rectangular shaped PM has better electromagnetic performances. Finally, a 25 kW OR‐PM machine prototype with rectangular shaped PM is manufactured and experimented. The predicted electromagnetic performance is validated by experimental results.